Faktor yang Berhubungan dengan Pemberian Susu Formula pada Bayi Usia 0-6 Bulan Tahun 2017 - Yesi Arisonaidah; Nurul Hidayah (Jurnal Endurance, 2019)
The government has long promoted exclusive breastfeeding for infants 0-6 months. However, in reality, mothers, especially in big cities, are more likely to choose formula milk either as a substitute or a companion to ASI in meeting the nutritional needs of their babies. In Indonesia, almost all babies get breast milk, but only about 61.5% of mothers give exclusive breastfeeding, while the expected target is 80%. This study aims to determine the factors associated with the provision of formula milk for infants aged 0-6 months in the working area of the Inpatient Health Center of Tenayan Raya pekanbaru in 2017. This type of research is quantitative with a cross sectional design, which was conducted from October 2016 to July of the year 2017. The population in this study were all mothers who had babies aged 0-6 months totaling 222 people and a sample of 143 people. The sampling technique uses consecutive sampling. Data collection uses primary data with a checklist sheet. Data processing includes editing, coding, scoring and tabulating. The analysis used is univariate and bivariate using chi-square. The results obtained by the value of value = 0,000 for education, value = 0,000 for work and value = 0,000 for information. From these results it can be concluded that there is a relationship between education, employment and information by providing formula milk to infants aged 0-6 months. It is expected for the Puskesmas to improve health promotion, counseling and counseling in order to increase maternal knowledge about the importance of exclusive breastfeeding. Pemerintah telah lama menggalakkan pemberian ASI eksklusif pada bayi 0-6 bulan. Namun, kenyataannya, kaum ibu khususnya di kota-kota besar, lebih cenderung memilih memberikan susu formula baik sebagai pengganti ataupun pendamping ASI dalam memenuhi kebutuhan gizi bagi bayi mereka. Di Indonesia hampir semua bayi mendapatkan ASI, namun hanya sekitar 61,5% ibu memberikan ASI eksklusif, sedangkan target yang diharapakn yaitu sebesar 80 %. Penelitian ini bertujuan untuk mengetahui faktor yang berhubungan dengan pemberian susu formula pada bayi usia 0-6 bulan di wilayah kerja Puskesmas Rawat Inap Tenayan Raya pekanbaru tahun 2017. Jenis penelitian ini adalah kuantitatif dengan desain cross sectional, yang dilakukan pada bulan Oktober 2016 hingga Juli tahun 2017. Populasi dalam penelitian ini adalah seluruh ibu yang mempunyai bayi usia 0-6 bulan berjumlah 222 orang dan sampel berjumlah 143 orang. Teknik sampling menggunakan consecutive sampling. Pengumpulan data menggunakan data primer dengan lembar checklist. Pengolahan data meliputi editing, coding, skoring dan tabulating. Analisa yang digunakan adalah univariat dan bivariat menggunakan chi-square. Hasil penelitian diperoleh nilai Pvalue =0,000 untuk pendidikan, Pvalue=0,000 untuk pekerjaan dan Pvalue=0,000 untuk informasi. Dari hasil ini dapat disimpulkan bahwa terdapat hubungan antara pendidikan, pekerjaan dan informasi dengan pemberian susu formula pada bayi usia 0-6 bulan. Di harapkan bagi pihak Puskesmas untuk meningkatkan promosi, konseling dan penyuluhan kesehatan guna meningkatkan pengetahuan ibu tentang pentingnya ASI Eksklusif.